Sistema de gestão integrado e o uso da água na alimentação coletiva - Lourenço, Maristela Soares (2003)
This dissertation investigates the management system on the food ndustr aoocc two v,ews: the employee s commitment and awareness about the organization. tne environrnent, and also, the water utilization on the food preparation process. which is composed by various steps. The study was done in three major Food and Nutrition Companies and the investigation methodology that was used has qualitative and quantftative approaches. lt was used a Stephen Fink questionnaire to evaluate the commitment of the empioyees to the organization, to the job and to their work coileagues. With respect of measuring the employees awareness, it was used a questionnaire developed by the author of the present work, containing questions about traíning and water utilization awareness. The questionnaires were applied to 107 employees of alI food preparation jobs, inciuding the managers of ali Food and Nutrition Unities (FNU) of the mentioned (ompanies. Among the 7 FNIJ s studied, only one has an integrated management system and an effective water use control in the food preparation processes, as well as training and procedures that focus on environmentai issues. The use of quality tools and water consumption coritrol is done only by the unity that has implemented the integrated management system, resulting in benefits related to water saving. it has been observed that it is necessary to take proactive actions fo minimize the water consumption and preserve the environment.